Molecular Imaging of Tau Protein: New Insights and Future Directions - Pizzarelli, Rocco; Pediconi, Natalia; Di Angelantonio, Silvia (Frontiers in Molecular Neuroscience, 2020)
Tau is a microtubule associated protein that is highly expressed in neurons and implicated in several cellular processes. Tau misfolding and self-aggregation give rise to proteinaceous deposits known as neuro-fibrillary tangles. Tau tangles play a key role in the genesis of a group of diseases commonly referred to as tauopathies; notably, these aggregates start to form decades before any clinical symptoms manifest. Advanced imaging methodologies have clarified important structural and functional aspects of tau and could have a role as diagnostic tools in clinical research. In the present review, recent progresses in tau imaging will be discussed. We will focus mainly on super-resolution imaging methods and the development of near-infrared fluorescent probes.